A pharmacokinetics phase 1 bioequivalence study of the trastuzumab biosimilar MYL‐1401O vs. EU‐trastuzumab and US‐trastuzumab. (31st July 2018) - Waller, Cornelius F.; Vutikullird, Apinya; Lawrence, Tracey E.; Shaw, Andrew; Liu, Mark Shiyao; Baczkowski, Mark; Sharma, Rajiv; Barve, Abhijit; Goyal, Parag; Donnelly, Charles; Sengupta, Nilanjan; Pennella, Eduardo J.
Abstract : Aims: Trastuzumab is a humanized monoclonal antibody that binds the human epidermal growth factor receptor 2 (HER2) oncoprotein and is an effective therapy for HER2‐overexpressing breast cancer. MYL‐1401O is a trastuzumab biosimilar. Here, we report results from a phase 1 study that investigated bioequivalence among MYL‐1401O, reference EU‐trastuzumab and US‐trastuzumab. Methods: This single‐centre, randomized, double‐blind, three‐arm, parallel‐group, phase 1 study was conducted in healthy adult male volunteers. Subjects were randomized 1:1:1 to receive a single 8 mg kg −1 dose of MYL‐1401O, EU‐trastuzumab or US‐trastuzumab as a 90‐min intravenous infusion. The primary objective was to assess PK similarity among all three products. Primary endpoints assessed were peak serum concentration (Cmax), area under the serum concentration–time curve from time of dosing to time of last quantifiable concentration and from time of dosing to infinity. Secondary endpoints included time of Cmax, elimination rate constant, half‐life, safety and immunogenicity. Results: Of 132 subjects enrolled (44/treatment), 120 (MYL‐1401O, n =  42; EU‐trastuzumab, n =  41; US‐trastuzumab, n =  37) were included in the PK analysis. The 90% confidence intervals of the ratios of geometric means for the primary endpoints were bounded within the predefined bioequivalence criterion of 80–125%. Secondary endpoints time of Cmax, elimination rate constant and half‐life were similar among groups. All treatment‐emergent adverse events were mild or moderate, similar across groups and no serious adverse events were reported. No treatment‐related antidrug antibodies were detected. Conclusions: MYL‐1401O was well tolerated and demonstrated PK and safety profiles similar to EU‐trastuzumab and US‐trastuzumab in healthy volunteers (ClinicalTrials.gov, NCT02594761).